Sumber Gejala dan Penyebab Konflik - Muhammad Abdullah Ubaidi; Rahmatullaillia Sari; Halimatus Sakdiyahi; Naila Jauhatoul Jinan; Mu’alimin Mu’alimin (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
Conflict is a complex social phenomenon and generally involves confrontation or dispute between individuals, groups, or countries. This article summarizes the sources, symptoms, and causes of conflict. Sources of conflict are often related to differences in values, beliefs, competition over resources, social inequality, and power politics. Symptoms of conflict include tension, violence, restrictions on freedom, and refugees. Causes of conflict can be triggered by differences in views, injustice, political instability, economic problems, discrimination, and political polarization. A deep understanding of the sources, symptoms and causes of conflict is important for effective prevention and resolution. One of the problems that often arises during change in an organization is conflict between members or between groups. One of the causes of conflict is resistance to change. .Conflict must not only be accepted and managed well, but must also be encouraged, because conflict is a force to bring about change and progress in institutions. Conflicts that occur in an organization due to human behavior as human resources will influence the effectiveness of the organization, therefore, every conflict that occurs is expected to be resolved through conflict management.